2021
DOI: 10.1097/md.0000000000024550
|View full text |Cite
|
Sign up to set email alerts
|

Single- or dual-antiplatelet therapy after transcatheter aortic valve replacement

Abstract: Background The evidence related to bleeding and thromboembolic events after transcatheter aortic valve replacement (TAVR) compared single antiplatelet therapy (SAPT) with dual antiplatelet therapy (DAPT) treatment are inconsistent. Moreover, there are some limitations such as small sample size and the risk of bias in existing studies. We will conduct a comprehensive systematic review and meta-analysis to explore the safety and efficacy of SAPT or DAPT after TAVR. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…7 Several studies have explored the use of antiplatelet therapy after TAVR. The results of several recent metaanalyses [29][30][31][32][33][34] have shown that the postoperative use of DAPT increases the risk of bleeding in patients compared with non-DAPT. The study by Kille et al 35 found that low platelet reactivity during clopidogrel treatment and the use of oral anticoagulation were the strongest predictors of perioperative bleeding events, which supports the recommendation that DAPT should not be routinely used after TAVR.…”
Section: Disscussionmentioning
confidence: 99%
“…7 Several studies have explored the use of antiplatelet therapy after TAVR. The results of several recent metaanalyses [29][30][31][32][33][34] have shown that the postoperative use of DAPT increases the risk of bleeding in patients compared with non-DAPT. The study by Kille et al 35 found that low platelet reactivity during clopidogrel treatment and the use of oral anticoagulation were the strongest predictors of perioperative bleeding events, which supports the recommendation that DAPT should not be routinely used after TAVR.…”
Section: Disscussionmentioning
confidence: 99%